BENEFITS AND SAFETY OF INSULIN THERAPY IN PEDIATRIC AND ADOLESCENT PATIENTS SUFFERING FROM CYSTIC FIBROSIS-RELATED DIABETES MELLITUS (CFRD): A SYSTEMATIC REVIEW - I Gusti Agung Nyoman Indira Prana; Fauna Herawati (Sean Institute, 2022)
About 40% of conditions of glucose intolerance occur in children aged 6-10 to adolescents with cystic fibrosis who are deficient in insulin. Hyperglycemia can occur before a person with cystic fibrosis is diagnosed with CFRD, with a significant reduction in clinical patients in glucose intolerance and an increased risk of lung organ failure. This systematic study aimed to determine the benefits and safety of providing insulin therapy in children and adolescents with Cystic Fibrosis-related Diabetes Mellitus (CFRD). The process of searching published literature through online databases such as Pubmed, Cochrane Library, ScienceDirect, and Google Scholar using the keywords Children, Insulin, Cystic Fibrosis, and Diabetes Mellitus using the Boolean operator